SERAPAN N TANAMAN JAGUNG (Zea mays L.) AKIBAT PEMBERIAN PUPUK GUANO DAN PUPUK HIJAU LAMTORO PADA ULTISOL WANGA - Imam Wahyudi (Universitas Tadulako, 2009)
High content of aluminum and low N availability in Ultisol are the important limiting factors for crop production. Hence, important efforts on management of Ultisol are increasing N availability for crop demand. Guano fertilizer and pruning of Lamtoro are source of organic matter used to improve the soil, although the two fertilizers still not yet have full attention. The present study was aimed to elucidate roles of Guano fertilizer and green manure of Lamtoro on Al concentration, N availability, crop growth and N uptake by maize in an Ultisol. The study was conducted in a glasshouse. Combination of the two fertilizers at two different rates of each fertilizer (10 and 20 ton/ha) and one control (no fertilizer added) resulted in nine treatments and they were arranged in a factorial randomized block design with three replicates. Results of the experiment showed that the application of Guano fertilizer and Lamtoro green manure significantly reduced Alexch concentration, increased soil pH, increased N availability, improved maize growth and increased N taken up by maize grown for 45 days.